CONDITION OF TUNA RESOURCES LANDED AT LABUHAN LOMBOK FISHING PORT, WEST NUSA TENGGARA PROVINCE - Gigentika, Soraya; Hilyana, Sitti; Amir, Sadikin; Waspodo, Saptono; Paryono; Umam, Misbahul; Tahir, Ahdiat Mardelaga; Bachri, Syaeful; Hasbullah, Lalu (Departemen PSP IPB, 2025)
West Nusa Tenggara (WNT) Province is one of the provinces in Indonesia that contributes to national tuna production, with Fisheries Management Area (FMA) 573 being the dominant area utilized by WNT fishermen. The high level of catch in FMA 573 poses a serious challenge to the availability of tuna, as these resources are currently classified as fully exploited and overexploited. Therefore, it is important to understand the production patterns and utilization characteristics of tuna fisheries at Labuhan Lombok Fishing Port in order to formulate sustainable tuna fisheries management strategies and encourage efforts to transition or optimize the utilization of FMAs that still have sustainable potential. The purpose of this study was to determine the types and production of tuna landed, as well as the conditions of its utilization at Labuhan Lombok Fishing Port. Data collection for this study was carried out in 2022 and 2023. Secondary data on tuna landings in WNT Province were obtained from the NTB Provincial Department of Marine Affairs and Fisheries, while secondary data on tuna landings at Labuhan Lombok Fishing Port were collected from the port management authority. The secondary fish landing data included monthly tuna production data for WNT Province and daily tuna landing production data for Labuhan Lombok Fishing Port. Descriptive statistical analysis and utilization level analysis were employed to analyze the collected data. The results of this study indicate that the average production of tuna landed at Labuhan Lombok Fishing Port during the period 2014 and 2016–2022 was 1,459.3 tons per year, of which approximately 87.17% was yellowfin tuna, 12.42% was bigeye tuna, and 0.41% was albacore. Meanwhile, the results of the utilization level analysis show that tuna fishermen at Labuhan Lombok Fishing Port were able to produce approximately 3.21% of yellowfin tuna, 3.73% of bigeye tuna, and 0.39% of albacore relative to the potential tuna resources in the Indian Ocean. Key words: Indian Ocean, Labuhan Lombok, sustainable potential, tuna, WNT